Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

If Cos(A+Y)/Cos(A-Y)=Cos2B , then prove that tan 2 B=(tanA)(tanY)

If Cos(A+Y)/Cos(A-Y)=Cos2B , then prove that tan2B=(tanA)(tanY)

Grade:

1 Answers

siddharth gupta
28 Points
6 years ago
COS(A+Y)/COS(A-Y)=(COS(A)COS(Y)-SIN(A)SIN(Y))/(COS(A)COS(Y)+SIN(A)SIN(Y))
DIVIDE NUMERATOR AND DENOMINATOR IN THE ABOVE EQN BY COS(A)COS(B)
ON DIVIDING THE ABOVE EQN BECOMES
(1-TAN(A)TAN(Y))/(1+TAN(A)TAN(Y))=COS(2B)=(1-TAN2(B))/(1+TAN2(B))
NOW YOU MAY EITHER CROSS MULTIPLY OR ON DIRECT OBSERVATION OF ABOVE EQN WE CAN SAY
TAN2B=TAN(A)TAN(Y)
WITH REGARDS 
SIDDHARTH GUPTA

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free